ZTE MRI improves detection of calcific deposits and differentiation between resorptive and formative phases in calcific tendinitis of shoulder - Ji Young Hwang; Hyein Yun; In Na Yoon; Min-Yung Chang; Minseong Kang; Sang-Jin Shin; Moon jung Hwang (Scientific Reports)
Abstract The purpose of study was to evaluate the diagnostic value of the ZTE sequence of shoulder MRI in patients with calcific tendinitis by comparing conventional sequences. Seventy-nine patients (43 patients with calcific tendinitis and 36 control group) who underwent both radiography and MRI including ZTE sequence were enrolled in our study. Two radiologists assessed the SNR, image quality, presence, size, multiplicity, shape, margin, signal intensity, composition, and location of calcific deposits on ZTE image, FSPDWI, and T2WI. The diagnostic performance was calculated with radiography as the standard of reference. The inter-reader agreement and differentiation of the resorptive phase and formative phase on ZTE were compared to that on FSPDWI and T2WI. A total 59 calcific deposits in 43 patients were found on radiography and classified into type 1 resorptive phases (n = 20) and type 2 formative phases (n = 39). ZTE image quality was for diagnostic use with substantial inter-reader agreement. Sensitivity and detection rate of ZTE image was better than those of FSPDWI and T2WI. The inter-reader agreement of ZTE image was equal to FSPDWI and better than T2WI. The features of calcific deposits on ZTE images were significantly different between two phases. In the resorptive phase, a greater percentage of calcific deposits showed irregular shapes, ill-defined margin, heterogeneous compositions on ZTE images. In conclusion, ZTE sequence may provide useful information for the diagnosis of calcific tendinitis of the shoulder.